From shrubs to urban dispersion: using biomimicry to generate a comfortable outdoor microclimate in New Cairo, Egypt. Issue 1 (2nd January 2023) - Coutry, M. N.; Elhalafawy, A.
ABSTRACT: This study examined how urban dispersion can act as passive thermal comfort method in New Cairo, Egypt. Using shrub dispersion patterns to determine the optimum dispersion pattern for urban settlements in hot climates. Shrubs' self-organised patterns were examined, then translated into mathematical equations that formed the basis of an algorithm to guide the redistribution of existing buildings via four proposals. These proposals were examined using the Universal Thermal Comfort Index to compare them to the existing urban dispersion patterns. The numerical and visual outcomes indicate that the proposed dispersion patterns can achieve more comfortable urban microclimate than the existing conditions.